Risk Factors Associated with Cardiac Autonomic Modulation in Obese Individuals - Camila Oliveira; Erika Aparecida Silveira; Lorena Rosa; Annelisa Santos; Ana Paula Rodrigues; Carolina Mendonça; Lucas Silva; Paulo Gentil; Ana Cristina Rebelo (Journal of Obesity)
Obesity leads to an imbalance in the autonomic nervous system, especially in increased sympathetic modulation and decreased vagal tone, and some anthropometric, metabolic, and lifestyle variables may increase the risk of developing cardiovascular disease. Objective. To analyze the association between cardiovascular autonomic modulation and biochemical and anthropometric markers, food intake, and physical activity level in severely obese individuals. Methodology. The present study is a cutout of a randomized clinical trial “Effect of nutritional intervention and olive oil in severe obesity” (DieTBra Trial), where the baseline data were analyzed. Anthropometric data, biochemical exams, heart rate variability (HRV), accelerometry, and 24 h recall (R24H) of obese patients (body mass index BMI ≥35 kg/m2) were collected. Results. 64 obese patients were analyzed, with a mean age of 39.10 ± 7.74 years (27 to 58 years). By HRV analysis, in the frequency domain, the obese had a higher predominance of sympathetic autonomic modulation (low frequency (LF) 56.44 ± 20.31 nu) and lower parasympathetic modulation (high frequency (HF) 42.52 ± 19.18 nu). A negative association was observed between the variables Homeostasis Evaluation Model (HOMA-IR) and HF (p=0.049). In the physical activity analysis, there was a negative association between moderate to vigorous physical activity and the sympathetic component (p=0.043), and for sedentary time (ST), there was a negative association with HF (p=0.049) and LF/HF (p=0.036) and a positive association with LF (p=0.014). For multiple linear regression, waist circumference (WC) and HOMA-IR values were negatively associated with HF (β = −0.685, p=0.010; β = −14.989, p=0.010; respectively). HOMA-IR (β = 0.141, p=0.003) and the percentage of lipids ingested (β = −0.030, p=0.043) were negatively associated with LF/HF. Conclusion. Among the cardiovascular risk variables studied, insulin resistance and central adiposity showed the greatest influence on cardiac autonomic modulation of obese, increasing the risk for cardiovascular disease.